Management of Caries-Related Visits to a Pediatric Hospital Emergency Department - Duong, Janice K.T. (My University, 2014)
Purpose: The purposes of this study were to: (1) identify characteristics of patients visiting a pediatric emergency department (ED) for dental caries and infection, (2) describe the medical and dental services provided to these patients, (3) quantify and compare treatment and wait times in the ED for dental caries and infection emergencies, and (4) examine the relationship between wait times in the ED and triage acuity scores, pain scores, and National Emergency Department Overcrowding Scale (NEDOCS). Methods: This is a descriptive study of data collected from a retrospective, cross-sectional, chart review of all after-hours patients receiving emergency dental treatment for dental caries and infection at Seattle Children's Hospital from January 1, 2008 through December 31, 2010. Demographics, triage acuity, pain scores, and medical/dental treatment and times were analyzed. Results: A total of 155 patients (99 males and 56 females) with dental caries and infection presented to the ED during the study period. Demographics and dental treatments were similar to previous studies. Mid-level triage scores were assigned to most patients (79%). Pain scores were moderate to severe for 40% of patients. The most frequently provided medical services were writing prescriptions (70%) and administration of medications in the ED (68%). There was a significant association between pain score and pain management; as pain scores increased, there was an increase in both administration and prescription of non-narcotic analgesics (p=0.043 and p=0.046, respectively) and narcotics (p=0.007 and p<0.001, respectively). The mean times were 77 minutes waiting for an ED physician, 55 minutes for dental treatment, and 238 minutes for overall length of stay (LOS). Dental consultation and treatment averaged 23% of time spent at the hospital. Higher pain levels resulted in increased overall LOS. On average, administration of medications in the ED significantly increased LOS by 73 minutes (p<0.001), and writing a prescription significantly increased LOS by 54 minutes (p<0.001). Twenty-one percent of patients needed hospital admission, and the mean admit length of stay for these patients was 40 hours. Conclusion: Dental treatment provided in a hospital ED is inefficient and time-consuming with significant healthcare resource utilization. Dental treatment accounted for only 23% of total time spent in the ED, and most patients required no advanced medical intervention. The economic implications of managing dental caries and infection in an ED are unfavorable for patients, hospitals, and third party payers. An outpatient dental clinic could provide treatment for most of these pediatric dental emergencies at significantly reduced cost in patient time and healthcare resources.
Thesis (Master's)--University of Washington, 2014
Keywords: Caries; Emergency dentistry; Emergency department; Health care utilization; Hospital dentistry; Pediatric dentistry; Dentistry; Medicine; dentistry